2011
DOI: 10.1007/s00418-011-0875-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DDX25 in nuage components of mammalian spermatogenic cells: immunofluorescence and immunoelectron microscopic study

Abstract: The localization of DDX25/GRTH and gonadotropin-stimulated RNA helicase was studied in the spermatogenic cells of rat, mouse, and guinea pig by immunofluorescence and immunoelectron microscopy (IEM). Immunofluorescence studies identified four kinds of granular staining: (1) fine particles observed in meiotic cells; (2) small granules associated with a mitochondrial marker, appearing in pachytene spermatocytes after stage V; (3) short strands lacking the mitochondrial marker in late spermatocytes; and, (4) larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…The NANOS1 signals were weaker than those observed for other nuage proteins such as DDX4 [23], DDX25 [21] and BRU-NOL2 [22]. As shown by immunofluorescence staining and dot blotting analysis, NANOS1 was abundantly present in the cytosol fraction.…”
Section: Immunoelectron Microscopic Localization Of Nanos1 In Nuage Amentioning
confidence: 72%
See 2 more Smart Citations
“…The NANOS1 signals were weaker than those observed for other nuage proteins such as DDX4 [23], DDX25 [21] and BRU-NOL2 [22]. As shown by immunofluorescence staining and dot blotting analysis, NANOS1 was abundantly present in the cytosol fraction.…”
Section: Immunoelectron Microscopic Localization Of Nanos1 In Nuage Amentioning
confidence: 72%
“…The present study showed that NANOS1 is also localized to the non-nuage structures, such as MAG, GB, RB, RA, Head cap of the step-17 spermatids, and outer dense fibers of flagella. Although the functions of MAG, GB, RB, and RA remain unknown, our previous studies have shown that DDX25 and BRUNOL2 are present in these structures [21,23]. The existence of nuage proteins such as BRUNOL2, DDX25 and NANOS1 in these structures suggests that these proteins may have biological functions there.…”
Section: Immunoelectron Microscopic Localization Of Nanos1 In Nuage Amentioning
confidence: 91%
See 1 more Smart Citation
“…From these studies a new step of nuage research was started. Previously, we investigated the localization of several nuage-resident proteins in the nuage structures of spermatogenic cells by immunoelectron microscopy (IEM) [22][23][24][25][26]. On the basis of localization of nuage proteins, including DDX4, DDX25, BRUNOL2, NANOS1, and MAEL, we reclassified the nuage into (1) aggregates of 60-90 nm particles (60-90P); (2) irregularly-shaped perinuclear granules (ISPG); (3) intermitochondrial cement (IMC); (4) satellite bodies (SB); and (5) chromatoid bodies (CB) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Cluster of 30 nm particles which were classified into the nuage by Russell and Frank [19] were not nuage because they did not contain any nuage proteins. In addition, we determined that several nuage proteins localize to spermatogenic cell-specific structures, including mitochondria-associated granules (MAG), 2 Journal of Histology granulated bodies (GB), reticulated bodies (RB), and ribosome aggregates (RA) [22][23][24][25][26]. These structures first appear in the cytoplasmic lobe of elongated step 10 spermatids and subsequently disappear in step 19 spermatids.…”
Section: Introductionmentioning
confidence: 99%